DAMPAK PEMBANGUNAN HOTEL CIBINONG CITY MALL TERHADAP PERUBAHAN KONDISI SOSIAL DAN EKONOMI MASYARAKAT RW 04 PAKANSARI CIBINONG - Novianto, Dicky; Syaiful, Syaiful; Aminda, Renea Shinta (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIKA Bogor, 2023)
Cibinong City Mall is one of the largest and grandest shopping centers in Bogor, which is located in the Pakansari area, Cibinong, Bogor, West Java. Strategically located in the central government area of Bogor Regency and 2 kilometers from the North Sentul toll gate. This mall started operating in 2013. Cibinong City Mall (CCM), is preparing the next step in the construction of Harris Hotel, by appointing PT Adhi Persada Gedung (APG) as the main contractor in the construction project.. The selection of APG as the main contractor is based on the credibility of the BUMN company which has succeeded in constructing many buildings in Indonesia. The number of hotels is feared to have an impact on the social and economic conditions of the community. The objectives of this study are 1) To examine the socio-economic characteristics of the population in the area around the hotel construction 2) To examine the effect of hotel construction on socio-economic conditions in Cibinong District. The analytical method used is the technique of collecting data through surveys in the form of interviews to obtain primary data. The results of the interview explained that 1) The characteristics of the social and economic conditions of the people of Cibinong District in the near, medium, and far areas were not much different. The level of awareness of public education is high. This is indicated by the SMA/SMK level that dominates in each area for both parents and children. The number of people who state that the income they get every month is sufficient to meet their daily needs and tertiary needs, 2) The effect of hotel development on socio-economic conditions in Cibinong District has positive and negative impacts. The direct and indirect impacts are seen in economic conditions where the direct impact provides new jobs for the surrounding community for the hotel construction process.